Progress in VLSI Design and Test 16th International Symposium, VDAT 2012, Shibpur, India, July 1-4, 2012. Proceedings - Rahaman, Hafizur; Chattopadhyay, Sanatan; Chattopadhyay, Santanu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 16th International Symposium on VSLI Design and Test, VDAT 2012, held in Shibpur, India, in July 2012. The 30 revised regular papers presented together with 10 short papers and 13 poster sessions were carefully selected from 135 submissions. The papers are organized in topical sections on VLSI design, design and modeling of digital circuits and systems, testing and verification, design for testability, testing memories and regular logic arrays, embedded systems: hardware/software co-design and verification, emerging technology: nanoscale computing and nanotechnology.
Keywords: Computer science; Logic design; Computer Communication Networks; Software engineering; Data structures (Computer science).; Computer software; Computer Science; Logic Design; Software Engineering/Programming and Operating Systems; Computer Communication Networks; Data Structures, Cryptology and Information Theory; Algorithm Analysis and Problem Complexity; Programming Techniques